1997
DOI: 10.1101/gad.11.20.2729
|View full text |Cite
|
Sign up to set email alerts
|

Chip, a widely expressed chromosomal protein required for segmentation and activity of a remote wing margin enhancer in Drosophila

Abstract: The mechanisms allowing remote enhancers to regulate promoters several kilobase pairs away are unknown but are blocked by the Drosophila suppressor of Hairy-wing protein (Suhw) that binds to gypsy retrovirus insertions between enhancers and promoters. Suhw bound to a gypsy insertion in the cut gene also appears to act interchromosomally to antagonize enhancer-promoter interactions on the homologous chromosome when activity of the Chip gene is reduced. Development of multicellular organisms requires precise tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
181
1
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(189 citation statements)
references
References 59 publications
2
181
1
4
Order By: Relevance
“…The LIM domain of LDBs contributes to the binding of transcription factors, including LIM-homeodomain, zinc-finger and basic helixloop -helix (bHLH) proteins (Agulnick et al, 1996;Jurata et al, 1996;Bach et al, 1997;Morcillo et al, 1997). Formation of protein complexes synergistically activates the expression of target genes Milán et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The LIM domain of LDBs contributes to the binding of transcription factors, including LIM-homeodomain, zinc-finger and basic helixloop -helix (bHLH) proteins (Agulnick et al, 1996;Jurata et al, 1996;Bach et al, 1997;Morcillo et al, 1997). Formation of protein complexes synergistically activates the expression of target genes Milán et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an alternative model involving proteins named facilitators that bring the enhancer and the promoter close to each other can be considered. Among these facilitators, the Drosophila Chip protein has been found to interact with Su(Hw) (Morcillo et al, 1997). Genetic evidence has shown that Su(Hw) becomes a more effective insulator when enhancerpromoter communication is weakened by mutations in Chip.…”
Section: Insulators and Gene Transcriptionmentioning
confidence: 99%
“…The data suggest the possibility of either novel LIM-HD proteins expressed in Clim1a-positive cell groups or, alternatively, a LIM-HD-independent role for Clim1a in these cells. Support for the latter scenario comes from studies on Drosophila segmentation, where CHIP, the Drosophila homolog of Clim2, appears to have broad functions beyond interacting with LIM proteins (Morcillo et al, 1997). CHIP is required for embryonic segmentation, and interacts with diverse homeodomain proteins by means of residues distinct from those that interact with LIM domains (Torigoi et al, 2000).…”
Section: A Role For Clim and Lmo Proteins In The Cortex Independent Omentioning
confidence: 99%